Pengaruh Jumlah Penduduk Terhadap Pertumbuhan Ekonomi Kabupaten Tebo Tahun 2016-2020 - Budi Darma (CITRA EKONOMI, 2021)
This research entitled The Effect of Total Population on Economic Growth in Tebo Regency in 2016-2020. This research aims to determine the effect of population on economic growth. The data used in this research is secondary data obtained from the website of BPS Tebo Regency and BPS Jambi Province. Data analysis used simple linear regression analysis, t test, and coefficient of determination (R2). The results showed that the largest population was in 2020 with a population of 360,193 people. The highest growth occurred in 2017 where there was an increase of 1.77% from the previous year. And the population grows by an average of 1.68% each year. For economic growth, the highest GRDP occurred in 2020 with an amount of Rp. 14,759. The highest economic growth development occurred in 2017 where there was an increase of 11.59% from the previous year. Then, the average economic growth was 6.19%. The population has a partial and significant effect on the economic growth of Tebo Regency in 2016-2020. The population has an influence of 93.7% on the economic growth of Tebo Regency in 2016-2020. Meanwhile, 6.3% which affects economic growth is influenced by other variables not examined in this study.